Detection of the minimum concentrations of α-lactose solution using high-power THz-ATR spectroscopy - Wang, Haiqing; Shi, Wei; Hou, Lei; Li, Chunhui; Zhang, Yusong; Yang, Lei; Cao, Juncheng (Frontiers in Bioengineering and Biotechnology, 2023)
Terahertz (THz) technology has emerged as a promising tool for the qualitative and quantitative identification of markers containing major diseases, enabling early diagnosis and staged treatment of diseases. Nevertheless, the detection of water-containing biological samples is facing significant challenges due to limitations in high-power THz radiation sources and high-sensitivity detection devices. In this paper, we present a designed and constructed set of Terahertz-Attenuated Total Reflection (THz-ATR) spectrometer for high-sensitivity detection of liquid biological samples, which can dynamically maintain the signal-to-noise ratio (SNR) of THz detection signal of liquid biological samples at 40-60 dB. Our high-power THz-ATR spectroscopy can identify and quantitatively detect α-lactose aqueous solution with a minimum concentration of 0.292mol/L. Moreover, we observed that the rate of change in the absorption peak position varied greatly between high and low concentration samples. Our high-power, high-sensitivity THz-ATR spectroscopy detection provides a rapid, accurate, and low-cost method for detecting disease markers such as blood and urine indicators. Additionally, this approach offers new perspectives for the refinement and in-depth detection of biomedical samples.